CHILDREN WITH ASD LEARNING ESL: BENEFITS AND CHALLENGES (Revista Inclusiones, 2019)
The article deals with the methodology of teaching ESL to children with the autism spectrum disorder (ASD), the creation of necessary environment, taking into account the peculiarities of ASD. It outlines the basic features of ASD, regarding it as a complex disorder and provides recommendations to parents and teachers in terms of ESL teaching and learning. The article also touches upon the issues of problematic behaviour and tantrums in the classroom, providing possible solutions of those problems. Among other methods Applied Behavior Analysis (ABA) is used. ABA therapy has proved to be efficient in teaching children with ASD and to avoid undesirable behaviour. The article specifically focuses on ESL learning computer applications and websites, which develop such skills as attention, quick reaction, and broaden the horizon. Many of them, having been developed by parents themselves, take into account specific interests and needs of an ASD child, for example, plain background, absence of background music, clear introduction of instructions, etc.